Pendampingan Pemanfaatan Media Sosial Untuk Promosi Dan Pemasaran Tahu Tempe Di Kota Manna - Ramahdani, Dita; Sachanovrissa, Silke; Subhi, Ramadan; Nurzam, Nurzam; Tambunan, Dennis Rydarto (Universitas Dehasen Bengkulu, 2024)
The world of marketing will definitely be influenced by rapid advances in technology, the digital world and the internet. The world is experiencing a shift from conventional (offline) to digital (online) marketing strategies. This digital marketing strategy has more. Digital marketing is the promotion and search for product markets through digital media online by utilizing various means, such as social networks, and allows potential consumers to obtain various information about products and carry out transactions via the internet. Mr. Yuli is a tofu and tempeh entrepreneur in the city of Manna, southern Bengkulu. This business was founded in 80 and he has been in this business for approximately 44 years. Providing online marketing training using social media so that this business can develop. By using product and distribution innovation methods.